2000
DOI: 10.1002/1098-2388(200007/08)19:1<3::aid-ssu2>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian cancer: Epidemiology, biology, and prognostic factors

Abstract: Ovarian cancer varies widely in frequency among different geographic regions and ethnic groups, with a high incidence in Northern Europe and the United States, and a low incidence in Japan. The majority of cases are sporadic, and only 5% to 10% of ovarian cancers are familial. The etiology of ovarian cancer is poorly understood. Models of ovarian carcinogenesis include the theory of incessant ovulation, in which a person's age at ovulation, i.e., lifetime number of ovulatory cycles, is an index of her ovarian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
412
1
24

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 616 publications
(457 citation statements)
references
References 90 publications
(90 reference statements)
7
412
1
24
Order By: Relevance
“…31,32 By using publicly available gene-expression profiling data, we have systematically screened the region on 8p22 for differentially regulated genes and identified TUSC3 as a candidate tumor suppressor gene in ovarian cancer. 14 In our current work, we validate our previous observations in a larger, completely independent patient population and demonstrate that the expression of TUSC3 in ovarian cancer may be regulated by promoter methylation.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 By using publicly available gene-expression profiling data, we have systematically screened the region on 8p22 for differentially regulated genes and identified TUSC3 as a candidate tumor suppressor gene in ovarian cancer. 14 In our current work, we validate our previous observations in a larger, completely independent patient population and demonstrate that the expression of TUSC3 in ovarian cancer may be regulated by promoter methylation.…”
Section: Discussionmentioning
confidence: 99%
“…4 Known risk/protective factors of ovarian cancer are reproductive and hormonal factors and family history. [5][6][7][8][9] A previous Swedish study estimated population-attributable fractions for epithelial ovarian cancer and found the highest contribution of 22.3% for reproductive factors, well above 2.6% for family history. 10 In population-based studies with medically verified diagnosis, the familial risk of invasive ovarian cancer has ranged between 2.0 and 3.0.…”
mentioning
confidence: 99%
“…1 An initial surgical approach is essential for aggressive cytoreduction and proper staging of the disease, since minimal residual tumor after surgery is a major factor of better response to chemotherapy and survival. 2 Intravenous combinated chemotherapy with taxol plus carboplatin is the current regimen of choice for the treatment of advanced ovarian cancer and is followed by a 50% complete pathologic remission rate.…”
mentioning
confidence: 99%